Ett röjningsröseområde i Farstorp – odling, begravning och ritual (AmS-Varia, 2020)
This paper problematises the categories grave and clearance cairn, based on source-material from Farstorp, Småland. A central point of departure for the analysis is landuse in a long-term perspective. Parts of a clearance-cairn site, comprising clearance-cairns, graves and constructions similar to graves although less well–built, were excavated. The latter were termed complex cairns. Exterior elements were kerbs and surface layers of fire-cracked stones. Interior features resembled cremation layers with fire-cracked stones. Inside and adjacent to these, burnt animal bones and other objects, including intact pots containing food, had been deposited. The main building material was clearance stones, plausibly from surrounding arable land. Features mainly date to Late Roman Iron Age and Migration Period. Fire-cracked stones and burnt animal bones are interpreted as waste from ritual meals, consumed during spring and autumn farm work. Depositions of grinding stones support the assumption that fertility of the land was an important ritual theme. Participants of these meals might be members of the household that held the land rights. A few human bones were deposited in each grave, possibly from deceased members of the owner family who might be expected to act in favour of their living descendants, to enhance fertility in general. Such deposits may also have demonstrated and consolidated land rights.